Youthsites : histories of creativity, care, and learning in the city. - Poyntz, Stuart R.; Sefton-Green, Julian; Fitzsimmons Frey, Heather (My University, 2023)
This book is an original study of the youth organizations in London, Toronto, and Vancouver that offer creative and arts programs mainly to youth from diverse and socially marginalized backgrounds. It describes a sector that is often not recognized, organizations that don't like being institutionalized, forms of education that exist outside the mainstream, types of aesthetic expression that often go unrecognized, and unusual learning and cultural opportunities for socially marginalized young people. Rooted in the history of community arts movements from the 1970s, Youthsites, or the non-formal youth arts learning sector, is now part of cities around the world. Technological change, shifts in educational discourses, changes in policy rhetorics, including a turn away from traditional public institutions and a decline in funding of formal public schooling have all impacted the growth of youth arts organizations. Yet there are to date no systematic studies of the history, structure, and development of this sector. Youthsites: Histories of Creativity, Care, and Learning in the City fills this gap and is the first book to develop an internationally comparative, evidence-based, structural analysis of the development of the youth arts sector. Based on an original 4-year study examining the history, priorities, and tensions within this sector between 1995 and 2015, Youthsites explores the organizations and people who are helping young people to become creators, citizens, or just themselves in times of austerity, crisis, and change.
Keywords: alternative education; non-formal education; youth arts organizations